Targeting the Brain Renin–Angiotensin System in Epilepsy: Possible Anticonvulsant Effects of Valsartan in Pentylenetetrazole-Induced Convulsions (Cuestiones de Fisioterapia, 2024)
Background: Epilepsy is one of the most prevalent chronic neurological disorders and is characterized by recurrent unprovoked seizures resulting from abnormal excessive neuronal discharge within the brain. Despite the availability of multiple antiepileptic drugs (AEDs), a considerable proportion of patients continue to experience uncontrolled seizures,